Isomeric Effect on the anticancer Behavior of two Zinc (II) complexes based on 3, 5‐bis(1‐imidazoly) pyridine: Experimental and Theoretical Approach. (28th March 2019) - Zhu, Mingchang; Song, Da; Liu, Ning; Wang, Kehua; Su, Junqi; Xiong, Meng; Zhang, Xi; Xu, Yuang; Gao, Enjun
Abstract : Two isomeric Zinc (II) complexes constructed by 3, 5‐bis(1‐imidazoly) pyridine has been synthesized and characterized by single crystal X‐ray diffraction, elemental analyses and infrared spectroscopy. The binding mode and ability of complex 1–2 with CT‐DNA were studied by UV and fluorescence spectra. The intrinsic binding constant K b ( K b1  = 2.305 × 10 4  M −1, K b2  = 3.095 × 10 4  M −1 ) and the observed association constant K obs ( K obs1  = 1.523*10 6  M −1, K obs2  = 2.057*10 6  M −1 ) indicated that the insertion ability of complex 2 with CT‐DNA is stronger than complex 1. Gel electrophoresis showed that complexes have a good ability to hydrolyze cleavage pBR322 plasmid DNA. The cytotoxicity and apoptosis studies showed that complexes exhibited excellent cytotoxic activity against HeLa cells, especially complex 2 had better growth inhibition than Cisplatin. Molecular docking study simulated the binding model of complexes with DNA (PDB:4av1), showing an imidazole plane of complex 2 can be inserted into a DNA base pair in relative parallel. Both complexes can be used as potential anticancer agents. Abstract : DNA (PDB code 4av1) docking with complex 1–2.